The Processes That Help Units Within Organizations Build Intellectual Capital - Khoja, Faiza (Journal of Knowledge Management Practice, 2009)
In this paper the author studies data collected from seventy-five unit heads from different industries to ascertain that in order for units to accumulate and enhance intellectual capital, they should develop strong intra-firm networks that foster absorptive capacity, and which itself is influenced by cultural values and practices. This study offers several managerial implications.
Keywords: Intra-firm social networks; Intellectual capital; Organizational culture; Absorptive capacity